PERTUNJUKAN BATOMBE: DESKRIPSI SINGKAT - Liza Oktasari (Jurnal Elektronik WACANA ETNIK, 2011)
This article describes batombe of Nagari Abai Sangir Solok Selatan Sumatera Barat. Batombe is a performance which shows pantun dialog between men and women. Batombe performed in batagak panghulu, marriage, and build a rumah gadang. There are functions on this performance. Those are entertaining, supporting, unifying, and learning media of the society.